Host Evasion by Burkholderia cenocepacia - Ganesan, Shyamala; Sajjan, Umadevi S. (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia cenocepacia is an opportunistic respiratory pathogen of individuals with cystic fibrosis (CF). Some strains of B. cenocepacia are highly transmissible and resistant to almost all antibiotics. Approximately one-third of B. cenocepacia infected CF patients go on to develop fatal “cepacia syndrome.” During the last two decades, substantial progress has been made with regards to evasion of host innate defense mechanisms by B. cenocepacia. Almost all strains of B. cenocepacia have the capacity to survive and replicate intracellularly in both airway epithelial cells and macrophages, which are primary sentinels of the lung and play a pivotal role in clearance of infecting bacteria. Those strains of B. cenocepacia, which express both cable pili and the associated 22 kDa adhesin are also capable of transmigrating across airway epithelium and persist in mouse models of infection. In this review, we will discuss how this type of interaction between B. cenocepacia and host may lead to persistence of bacteria as well as lung inflammation in CF patients.